Korelasi Pengetahuan Bencana Banjir Rob Dengan Tingkat Kesiapsiagaan Masyarakat Pesisir Pantai - Saipiatuddin (Jurnal Penelitian Pendidikan Geografi, 2022)
Muara Gembong coastal topography is classified as a sloping topography, which allows water from the Java Sea to more easily enter the mainland when sea level rises. As a result of the tidal flood, it is very important to know the level of community knowledge about preparedness attitudes so that if there is a tidal flood, the community is more ready to save themselves. The purpose of this study was to determine the relationship between the level of knowledge and the coastal community's tidal flood preparedness in the subdistrict of Muara Gembong, Bekasi Regency, West Java. The approach used is cross sectional, which is measuring data only at one time, but that does not mean that the measurements are only carried out on the same day or time, but that the variables are measured only once, so there is no follow-up on the variables studied. The sampling technique used in this research is purposive sampling with a total sample of 121 respondents. There are 48 respondents who have a good level of knowledge have a good level of preparedness, while 20 respondents with a low level of knowledge have a low level of preparedness. Knowledge is the main factor of tidal disaster preparedness. The results of the relationship between knowledge and preparedness for tidal floods have a value of p = 0.000 (p<0.05) so that there is a relationship between knowledge and preparedness for tidal floods, besides that it can be said that if the level of knowledge is good, the level of disaster preparedness is also good.